THE SEARCH FOR NEUROPROTECTIVE COMPOUNDS AMONG NEW ETHYLTHIADIAZOLE DERIVATIVES - R. F. Cherevatenko; O. V. Antsiferov; S. Y. Skachilova; M. V. Pokrovsky; V. V. Gureev; I. I. Banchuk; A. Y. Banchuk; M. I. Golubinskaya; A. A. Syromyatnikova; I. S. Rozhkov; A. A. Mostovykh (Фармация и фармакология (Пятигорск))
The aim of the study is to search compounds with neuroprotective properties among new ethylthiadiazole derivatives in simulated traumatic brain injury.Materials and methods. The experiment was carried out on 78 white male rats 270±20 g line “Wistar” 5–6 months of age and 120 outbred sexually mature mice weighing 20±2 grams. The article describes the search for compounds with neuroprotective properties among new ethylthiadiazole derivatives under the codes LKHT 4–15, LKHT 10–18, LKHT 11–18, and LKHT 12–18 in experimental traumatic brain injury in rats. Acute toxicity of the compounds was studied. Pharmacological screening was performed using behavioral and neurological research methods. The McGraw stroke score scale modified by I.V. Gannushkina and the mNSS psychometric scale were used in the study. The open field and Rota-rod tests were used to assess the behavioral status of the animals.Results. The compound-LKHT 12–18 at a dose of 50 mg/kg was detected as a leader. In pharmacological correction of pathology, this compound had the lowest percentage of fatality among the studied compounds (8%), the severity of neurological deficit was significantly reduced, the lowest scores and a higher level of motor activity of the limbs were registered. The number of rearing in the group of animals receiving the compound LKHT 12–18 at the dose of 50 mg/kg increased by 1.5 times, statistically significant (p<0.05) in comparison with the control group. Based on the results of the “Rota-rod” test, the total time of holding animals on the rod for 3 attempts was statistically significantly different in the groups administered with LKHT 12–18 derivatives (1.5 times longer) at the dose of 50 mg/kg compared with the control (p<0.05).Conclusion. Based on the results obtained in this study, it is planned to study in more detail the compound LKHT 12–18 at the dose of 50 mg/kg.